Mobile App for IoT-Based Home Security System with Fingerprint Access Control - Wahid, Abdul; Hidayat, Rahmat; Riska, Muhammad (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
This study investigates the development and evaluation of an Android-based security system for residential areas, focusing on entrance and exit gate control. Recognizing the limitations of existing systems, we propose an